The Crucial Role of Sufi Order in Developing Emotional and Spiritual Intelligence and Shaping Social Integrity - Rusdi; Zulkifli (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The development of social interaction within Sufi Order (tarekat) offers a unique pathway to cultivate social piety in society. Rooted in the spiritual teachings and practices of the tarekat, this approach plays a pivotal role in enhancing emotional and spiritual intelligence (ESQ) among its members. This qualitative study, based on an extensive review of relevant literature, seeks to explore how the tarekat contributes to the growth of ESQ and its broader implications for fostering social piety. The findings reveal that the principles of maqāmat and aḥwal, central to tarekat teachings, significantly enhance both emotional and spiritual intelligence. This, in turn, encourages social piety, as demonstrated through the noble character and community-oriented actions of tarekat members. The research underscores the strong connection between tarekat practices and the development of ESQ, showing how this spiritual tradition serves as a vital religious social movement—one that not only deepens inner spiritual growth but also actively promotes social responsibility and engagement.